Development Conditions for Family Farming: Lessons From Brazil. (October 2015) - Medina, Gabriel; Almeida, Camila; Novaes, Evandro; Godar, Javier; Pokorny, Benno
Highlights: We need realistic assessments of the development conditions faced by family farmers. Most of the Brazilian family farmers do not fit into the modernization paradigm. Alternative development pathways have to be developed based on local initiatives. Summary: There is a renewed global interest in support of family farming becoming a more competitive sector, contributing to poverty alleviation, food security, and economic growth. This paper explores the development conditions faced by family farmers across Brazil. We not only reveal a potential for development, represented by the great number of family-based rural households, but also present several structural constraints faced by most family farmers, as well as great discrepancies among regions. We argue for encouraging the existing family farming potential by designing policies that consciously target specific regional challenges and avoid excluding segments not fitting into the modernization paradigm.